Does land degradation have an aggravating effect on the multidimensional poverty of rural households? Empirical verification of Burkina Faso - Abdoul Rahmane Ouedraogo; Didier Tibi Zoungrana; Richard Kouame Moussa (Cogent Social Sciences)
Land degradation is a real obstacle to achieving the Sustainable Development Goals. The objective of this article is to analyze the effect of land degradation on household poverty in Burkina Faso. To do this, the recursive bivariate probit model and the instrumental variable probit model (IV-probit) were used on data from the Harmonized Survey of Household Living Conditions to account for potential endogeneity between the explained and explanatory variables. The results indicate that land degradation influences the multidimensional poverty of rural households. Land degradation worsens the level of multidimensional poverty of rural households by 42.63% points. Based on these findings, there is a need for sustainable land management policies to reduce the effects of land degradation in rural areas in order to address challenges related to health, education and household living standards, thereby improving their level of non-monetary well-being.